2017
DOI: 10.1002/bit.26294
|View full text |Cite
|
Sign up to set email alerts
|

A 9‐pool metabolic structured kinetic model describing days to seconds dynamics of growth and product formation by Penicillium chrysogenum

Abstract: A powerful approach for the optimization of industrial bioprocesses is to perform detailed simulations integrating large-scale computational fluid dynamics (CFD) and cellular reaction dynamics (CRD). However, complex metabolic kinetic models containing a large number of equations pose formidable challenges in CFD-CRD coupling and computation time afterward. This necessitates to formulate a relatively simple but yet representative model structure. Such a kinetic model should be able to reproduce metabolic respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 51 publications
(99 reference statements)
0
45
0
Order By: Relevance
“…We assume that the specific glucose uptake rate (q s ) during a complete cycle is a hyperbolic function of C s , according to q s = normalqsnormalmaxnormalCnormalsKs+Cs. With the estimated parameters qnormalsmax = 0.0417 mol CmolX −1 h −1 and K s = 7.8 μM (Tang et al ., ), the q s profiles in the IFRs of 3 min and 6 min can be reproduced very well (Fig. S2), but not in the 30 s IFR.…”
Section: Resultsmentioning
confidence: 97%
“…We assume that the specific glucose uptake rate (q s ) during a complete cycle is a hyperbolic function of C s , according to q s = normalqsnormalmaxnormalCnormalsKs+Cs. With the estimated parameters qnormalsmax = 0.0417 mol CmolX −1 h −1 and K s = 7.8 μM (Tang et al ., ), the q s profiles in the IFRs of 3 min and 6 min can be reproduced very well (Fig. S2), but not in the 30 s IFR.…”
Section: Resultsmentioning
confidence: 97%
“…Haringa et al () integrated the 9‐pool penicillin model of Tang et al () into their full‐scale CFD simulation, observing a 33% loss in production rate and yield under chemostat conditions and good agreement with industrial production rate dynamics under fed‐batch conditions (Figure a). In the 9‐pool metabolic model, the glucose uptake rate (qs) is subject to transporter control, where the availability of transporter (XE,11) is controlled by growth rate µ (h −1 ) and the penicillin producing enzyme is inhibited by the lumped metabolic pool of glycolytic intermediates (Xgly; Tang et al, ). However, during the feast‐famine cycles, the simulation results showed that the growth rate oscillated between 0 and 0.15 hr −1 with the average value of 0.03 hr −1 , and the pool size of the glycolytic intermediate oscillates between 0 and 50 µmolC/gDW with the average value of 25 µmolC/gDW (Haringa et al, ).…”
Section: Through the Organism's Eyes: The Interaction Between Hydrodymentioning
confidence: 95%
“…As an example, as shown in Figure , our research group has developed and validated standard operating procedures (SOPs) for fast sampling, quenching, and efficient extraction of metabolites as well as preparation of U‐ 13 C metabolites as internal standards from P. chrysogenum to allow for global analysis of the metabolome under both steady‐state and nonstationary conditions (Wang, Chu, et al, ). This protocol has been exactly followed in our previous studies, which delivered invaluable information for in silico metabolic modeling and revealed regulatory mechanisms in response to genetic or environmental perturbations (Tang et al, ; Wang, Chu, et al, ; Wang, Chu, et al, ; Wang, Wu, et al, ; Wang, Zhao, et al, ; Wang, Zhao, et al, ).…”
Section: Quantitative Metabolomics and Its Application In Systems Metmentioning
confidence: 99%
See 2 more Smart Citations